2021
DOI: 10.51791/njap.v21i1.1096
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Phenotypic and Genetic Correlations in West African Dwarf Goats

Abstract: Records on 848 West African dwarf goat kids and 220 kiddings over a period of eight year's (1982-1989) were analyzed. The records were used to provide estimates of phenotypic and venetic correlations among parity, kidding interval, litter size at birth and body weight at various ages. Plenotypic correlation coefficients of +0.33 (P<0.01) and -0,17 (P<0.01) were obtained when parity was correlated with litter size at birth and kidding interval respectively. Phenotypic correlations among body weights were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The gestation length (GL) values obtained in this study were in line with what has been reported in the literature. Values between 29 to 33 days were reported by [15]. 28.10 to 30.40 days and 29.92 days were reported for some breeds of rabbits in Southern and Northern Nigeria [14].…”
Section: Discussionmentioning
confidence: 89%
“…The gestation length (GL) values obtained in this study were in line with what has been reported in the literature. Values between 29 to 33 days were reported by [15]. 28.10 to 30.40 days and 29.92 days were reported for some breeds of rabbits in Southern and Northern Nigeria [14].…”
Section: Discussionmentioning
confidence: 89%